Exploring nurses perceived self-efficacy and mental health competency for enhancing psychiatric care delivery in non-psychiatric settings - Ahmad A. Abujaber (14586054) (2025)
Background Nursing care is essential for providing high-quality, safe, and person-centered care, particularly for patients with mental health diagnoses. Mental illness poses significant global health challenges, and nurses often encounter difficulties in delivering care due to negative attitudes, poor mental health literacy, and fear, especially in non-psychiatric settings. Objective This study aims to investigate the perceived self-efficacy and mental health competency among nurses delivering psychiatric care in non-psychiatric settings. Methods A quantitative descriptive-cross-sectional design was employed. The study involved nurses from various non-psychiatric hospital settings, selected through convenience sampling to ensure a diverse representation in terms of experience, educational background, and exposure to psychiatric care. Participants' perceived competencies were assessed using the Behavioral Health Care Competency (BHCC) survey, while self-efficacy was measured using the Nursing Professional Self-Efficacy Scale—Version 2 (NPSES2). Data analysis Statistical analysis conducted using SPSS version 26, focusing on descriptive and inferential statistics at a significance level of p < 0.05 (two-tailed). Result Among 280 nurses, significant differences were found in nurse-perceived BHCC and NPSE based on training, with a notable correlation between perceived BHCC and NPSES, while sociodemographic factors like sex and education showed no significant impact. Conclusion The research suggests the need for educational and training programs for non-psychiatric nurses to address the gap in patient care. Extensive training and education equip nurses to deliver optimal care and compassion for patients with psychiatric demands. Other Information Published in: Applied Nursing Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apnr.2025.151959